How East Asians View Democracy 2008
DOI: 10.7312/chu-14534-007
|View full text |Cite
|
Sign up to set email alerts
|

5. Developing Democracy Under a New Constitution in Thailand

Abstract: Hopes for democracy in Thailand rest largely on impacts of the Constitution of 1997, influencing the electoral process. Although democracy has been developing steadily since 1978, the new constitution represents a step-level shift in the movement toward full democracy. Not only does the new constitution radically revise the systems of electoral democracy, it also creates new institutions for democratic governance that parallel elections as major instruments of democratic authority. Three institutions are of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…These variables were: (1) gender, a binary 0-1 variable, which assumed the value 1 for males and 0 for females; (2) continuous measure of age; (3) a 4-point scale of education, which assumed the value 3 for a doctoral degree and 0 for no university degree, with higher values indicating a higher level of education; (4) a dummy variable for experience in business, which assumed the value 1 for those who had been a businessperson and 0 for those who had not; (5) a dummy variable for experience in local government, which assumed the value 1 for those who had been a local government politician and 0 for those who had not; (6) a dummy variable for experience in the House, which assumed the value 1 for those who used to be a House member and 0 for those who had not; (7) a dummy variable for Democrat membership, which assumed the value 1 for House members from the Democrat Party and 0 for those from other parties; (8) a dummy variable for Pheu Thai membership, which assumed the value 1 for House members from Pheu Thai Party and 0 for those from other parties; (9) a dummy variable for the degree of urbanisation, which assumed the value 1 for House members who were elected from the more-developed constituencies of Bangkok and 0 for those who were elected from the less-developed constituencies of all other provinces; and (10) continuous measure of the number of candidates in each constituency. According to previous research on the electoral behaviour of Thai voters (Albritton & Thawilwadee, 2008;Nelson, 2013;Stithorn, 2012) and the socio-political relationships between voters and their elected representatives (Askew, 2008;Bowie, 2008;Nishizaki, 2011;Walker, 2008), a greater electoral advantage in a House of Representatives election could be expected for candidates who were male, older, had a higher degree of education, had experience in business, had experience in local government office, had previously held a seat in the House of Representatives, were members of either the Democrat or Pheu Thai Party, and were elected by a rural constituency, regardless of the number of candidates in that constituency.…”
Section: Methodsmentioning
confidence: 99%
“…These variables were: (1) gender, a binary 0-1 variable, which assumed the value 1 for males and 0 for females; (2) continuous measure of age; (3) a 4-point scale of education, which assumed the value 3 for a doctoral degree and 0 for no university degree, with higher values indicating a higher level of education; (4) a dummy variable for experience in business, which assumed the value 1 for those who had been a businessperson and 0 for those who had not; (5) a dummy variable for experience in local government, which assumed the value 1 for those who had been a local government politician and 0 for those who had not; (6) a dummy variable for experience in the House, which assumed the value 1 for those who used to be a House member and 0 for those who had not; (7) a dummy variable for Democrat membership, which assumed the value 1 for House members from the Democrat Party and 0 for those from other parties; (8) a dummy variable for Pheu Thai membership, which assumed the value 1 for House members from Pheu Thai Party and 0 for those from other parties; (9) a dummy variable for the degree of urbanisation, which assumed the value 1 for House members who were elected from the more-developed constituencies of Bangkok and 0 for those who were elected from the less-developed constituencies of all other provinces; and (10) continuous measure of the number of candidates in each constituency. According to previous research on the electoral behaviour of Thai voters (Albritton & Thawilwadee, 2008;Nelson, 2013;Stithorn, 2012) and the socio-political relationships between voters and their elected representatives (Askew, 2008;Bowie, 2008;Nishizaki, 2011;Walker, 2008), a greater electoral advantage in a House of Representatives election could be expected for candidates who were male, older, had a higher degree of education, had experience in business, had experience in local government office, had previously held a seat in the House of Representatives, were members of either the Democrat or Pheu Thai Party, and were elected by a rural constituency, regardless of the number of candidates in that constituency.…”
Section: Methodsmentioning
confidence: 99%
“…This variable is classified as a 4-point scale variable identifying the type of area in which respondents live: 0 for village; 1 for small or middle-sized town; 2 for suburb of large town or city; and 3 for a city or metropolitan area. Previous studies on the effects of education on voting behaviour at general elections in Thailand have shown that voters with a lower level of education are more likely to turn out and vote than voters with higher level of education (Albritton and Bureekul 2008). In this study, the survey question that asked respondents about their highest level of education is used as a measure of education, on a scale ranging from no formal education (0) to doctoral degree or equivalent (8).…”
Section: Methodsmentioning
confidence: 99%
“…Debates about good governance have been decisively shaped by intergovernmental organizations in the context of development cooperation. Essentially, actions to foster good governance focus on mitigating two undesirable traits: the unrepresentative character of governments and the inefficiency of non-market systems (Albritton and Bureekul, 2009). As Bøås (1998, p. 119) states: "the World Bank operationalized 'bad governance' as personalisation of power, lack of human rights, endemic corruption and un-elected and unaccountable governments.…”
Section: Political-institutional Preconditions: Democracy Good Govern...mentioning
confidence: 99%